Pharmaceutically active micropollutants: origin, hazards and removal - Gupta, Anuradha; Kumar, Sandeep; Bajpai, Yashi; Chaturvedi, Kavita; Johri, Parul; Tiwari, Rajesh K.; Vivekanand, V.; Trivedi, Mala (Frontiers in Microbiology, 2024)
Micropollutants are silent killer, untill few years back, due to lack of awareness about them, major focus was on management and bioremediation of macro pollutants only. Pharmaceutically active micropollutants are one of the causes of development of genetically modified microbes in nature, as well as MDR (Multi Drug Resistant) bacterial strains. It is important to find out methods and means of control and bioremediation of such micropollutants in our environment more specifically in Field Code Changed waterbodies. The proposed manuscript identifies and classified types of pharmaceutically active micropollutants. All possible methods of treatments as well as their control and bioremediation.